2011
DOI: 10.1002/jrs.2957
|View full text |Cite
|
Sign up to set email alerts
|

A background elimination method based on linear programming for Raman spectra

Abstract: In this paper, we consider a new background elimination method for Raman spectra. As a background is usually slowly varying with respect to wavelength, it could be approximated by a slowly varying curve. However, the usual curve-fitting method cannot be applied because there is a constraint that the estimated background must be beneath a measured spectrum. To meet the requirement, we adopt a polynomial as an approximating function and show that background estimation could be converted to a linear programming p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…In the literature Raman background subtraction has been conducted using a variety of methods including piecewise linear functions [26], cubic splines [27] and quadratic functions [28]. In the current work it was found that the background in the interval between 1300 and 2000 cm -1 , where no Raman signal should be detected, was best fit using an exponential function and this was then used for background subtraction.…”
Section: Raman Spectramentioning
confidence: 84%
“…In the literature Raman background subtraction has been conducted using a variety of methods including piecewise linear functions [26], cubic splines [27] and quadratic functions [28]. In the current work it was found that the background in the interval between 1300 and 2000 cm -1 , where no Raman signal should be detected, was best fit using an exponential function and this was then used for background subtraction.…”
Section: Raman Spectramentioning
confidence: 84%
“…Many others have proposed various theories to pre-process the Raman spectra to get rid of the substrate background contribution. [16,[19][20][21][22][23][24] New trend in recent decade is towards lab-on-a-chip applications for live cell Raman imaging. [25,26] Lab-on-a-chip requires fabrication of substrates to achieve enclosed fluidic compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Also within certain range of concentrations, the intensities of Raman spectrum are approximately linearly related to the concentration of each pure component [29]. So the relation between the intensities of Raman spectra and the concentrations of components of compounds can be represented as the full spectrum calibration model: (1) with the matrix being the mixture Raman spectra of compounds, the matrix representing the mixing concentrations of pure components in each compound, and the matrix being the unknown source Raman spectra of each pure component in the compounds. Rows of are background intensities of Raman signals.…”
Section: A Multivariate Calibration Modelsmentioning
confidence: 99%